(3MRH ShjOGfs - (3YHO Gddg Hf Ydj Hf YHO GdQMef ShjOGf GdOedjLj,J (B1234 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf Edi BNQgG Gddg dG Edg EdG gh hGdMi Gdbjhe GdBjI TgO Gddg GdBjg bd Gddge eGdc Gdedc s
(3BNQgG (B:s
(3Gddge Efi CYhP Hc ef ShA GdbVGA hef OQc GdTbGA hef TeGJI GdCYOGA hef LgO GdHdGA Ke SHMGf dGdg hHMeOg eGFg Gddge Udi Ydi SjOfG eMeO hCRhGLg hPQjJg NeSjf hGdMeO ddg QH GdYGdejf Je HMeO dGdg hYhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3HgG fXGe GdJYbjIs
(3HBNQg ahGFO JUhas
(3hgh MRH ddeDda jbQC UHGMkG heSGAkG hHBNQ s
(3ai U (B122 (3cjS GdHQcI HChdg fbhd hahGFO eNJdaI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B89s
Keywords: (3GdeLGejYs